Sleep disturbance and memory dysfunction in early multiple sclerosis. Issue 6 (5th May 2021) - Sumowski, James F.; Horng, Sam; Brandstadter, Rachel; Krieger, Stephen; Leavitt, Victoria M.; Katz Sand, Ilana; Fabian, Michelle; Klineova, Sylvia; Graney, Robin; Riley, Claire S.; Lublin, Fred D.; Miller, Aaron E.; et al.
Abstract: Objective: Sleep‐dependent memory processing occurs in animals including humans, and disturbed sleep negatively affects memory. Sleep disturbance and memory dysfunction are common in multiple sclerosis (MS), but little is known about the contributions of sleep disturbance to memory in MS. We investigated whether subjective sleep disturbance is linked to worse memory in early MS independently of potential confounders. Methods: Persons with early MS ( n = 185; ≤5.0 years diagnosed) and demographically matched healthy controls ( n = 50) completed four memory tests to derive a memory composite, and four speeded tests to derive a cognitive efficiency composite. Z‐scores were calculated relative to healthy controls. Sleep disturbance was defined by the Insomnia Severity Index score ≥ 10. ANCOVAs examined differences in memory and cognitive efficiency between patients with and without sleep disturbance controlling for potential confounds (e.g., mood, fatigue, disability, T2 lesion volume, gray matter volume). Comparisons were made to healthy controls. Results: Seventy‐four (40%) patients reported sleep disturbance. Controlling for all covariates, patients with sleep disturbance had worse memory ( z = −0.617; 95% CI: −0.886, −0.348) than patients without disturbance (z = −0.171, −0.425, 0.082, P = .003). Cognitive efficiency did not differ between groups. Relative to healthy controls, memory was worse among patients with sleep disturbance, but not among patients without sleep disturbance. Interpretation: Sleep disturbance contributes to MS memory dysfunction, which may help explain differential risk for memory dysfunction in persons with MS, especially since sleep disturbance is common in MS. Potential mechanisms linking sleep disturbance and memory are discussed, as well as recommendations for further mechanistic and interventional research.